2007
DOI: 10.1111/j.1365-2230.2007.02455.x
|View full text |Cite
|
Sign up to set email alerts
|

Local expression of TAP-1 and MHC-I molecules and their relationship in condyloma acuminatum

Abstract: These results suggest that HPV may evade immune recognition by downregulating MHC-I cell surface expression via decreased TAP-1 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Knowledge regarding the molecular mechanism culminating in the down-regulation of TAP1 is limited, however, the corollary relationship suggests a posttranscriptional mechanism. More recently, Tao et al (19) found a significant decrease in TAP1 mRNA among specimen collected from women with condyloma acuminatum compared with those collected from healthy women.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Knowledge regarding the molecular mechanism culminating in the down-regulation of TAP1 is limited, however, the corollary relationship suggests a posttranscriptional mechanism. More recently, Tao et al (19) found a significant decrease in TAP1 mRNA among specimen collected from women with condyloma acuminatum compared with those collected from healthy women.…”
Section: Discussionmentioning
confidence: 98%
“…Down-regulation of MHC class I expression has been noted in many diseases, in particular those associated with HPV such as recurrent respiratory papillomatosis, condyloma acuminatum, and cervical cancer (5, 1719). In a number of studies, down-regulation of MHC class I correlated with down-regulation of TAP1 , suggesting a causal link between altered expression of TAP1 and MHC-1 (6, 1820).…”
Section: Discussionmentioning
confidence: 99%
“…Although CD107-expressing cells have been identified in both groups, this marker was not present in the majority of inflammatory cervical cells, suggesting that HPV can somehow avoid the induction of an effective cellular immunity as well as the immune surveillance. One of the possible explanations was described by Tao et al (2007) that observed a concomitant decrease in the expression of both TAP-1 and MHC-I antigens in condiloma acuminatum compared with normal cervix. These observations suggested that HPV might block TAP-1 expression and thereby decrease MHC-I assembly and expression by limiting peptide entry into the rough endoplasmatic reticulum, abrogating the CD8 T cell recognition.…”
Section: Discussionmentioning
confidence: 95%
“…[571][572][573] The gene located at 2p21-p24 has not been identified, but it has been reported as a second locus in a French family with EV. 637 Condylomas in all age groups are recurrent in up to one-third of cases. 574,575 In addition to the plane warts, reddish-brown patches and lesions resembling scaling pityriasis versicolor and seborrheic keratosis develop, 576,577 with the eventual compli-down-regulating MHC-I surface expression.…”
Section: Epidermodysplasia Verruciformismentioning
confidence: 99%
“…635 This appears to result from a cellmediated immune response, 636 involving CD8 + cytotoxic T-lymphocytes. 637 The virus attempts to evade immune recognition by oncoproteins E6 and E7 contribute to oncogenesis in multiple ways. They also modulate the expression of p16 and human telomerase reverse transcriptase (hTERT).…”
Section: Condyloma Acuminatummentioning
confidence: 99%